Effectiveness of an educational neuroscience-based curriculum to improve academic achievement of elementary students with mathematics learning disabilities - Eskandar Fathiazar; Arash Mani; Yousef Adib; Zahra Sharifi (Tabriz University of Medical Sciences, 2020)
Background: The present study evaluated the effectiveness of a curriculum based on educational neuroscience on improving academic achievement in elementary students with mathematical learning disorder in Shiraz. Methods: This is a quasi-experimental research which was done on students with math learning disabilities from grades two to six in Shiraz District 2 and 4. 47 students fulfill the inclusion criteria, due to the exclusion criteria 31 students enrolled in the study. They are randomly assigned to experimental and control groups. All of them completed the pre and post-test training in the control group was based on the traditional teaching style and the curriculum patterns that were implemented. The training in the experimental group was based on educational neuroscience curriculum model. Differences are considered statistically significant at P≤0.05 and 95% confidence interval of the difference is considered. Results: The results showed that the mean of the control and experimental groups in numerical understanding variable was respectively: 28.60 and 36.87, in numerical production variable was: 15.13 and 20.06, in numerical calculation variable was: 8.80 and 13.62. The level of significance in the group in all three variables of numerical understanding, numerical production and numerical calculation was 0.001, which means that the experimental group performed better in the post-test than the control group. Conclusion: Educational neuroscience interventions such as the underlying math learning skills can be an effective approach in the treatment of math learning disabilities, the use of this curriculum has also directly improved attention structures and indirectly improved learning disabilities.